Influence of Heat Input On Mechanical Properties of Tungsten Inert Gas Welded Joint - J. Sinebe; L. C. Enyi (Journal of Applied Sciences and Environmental Management)
Welding is key sector in the manufacturing industry, and plays a critical role in making possible joints of different materials is achievable. Nevertheless, certain attributes of the welding process must be addressed, to ensure joints durable and reliable are produced. Hence, the objective of this paper is to evaluate the influence of heat input on the mechanical properties of a Tungsten Inert Gas (TIG) welded joint.  Data obtained reveals that the most stable bead width is recorded at a low heat input. Therefore, maintaining and controlling the heat input is capable of guaranteeing the value of the bead width. Also the relatiobship between critical weld properties, which is the bead width and the tensile strength, as obtained from variation arising from the heat input, shows that the most maximum bead width is recorded at a very high tensile strength. An indication that the heat input has a corresponding effect on the bead width and tensile strength of the weld.